Genetic analysis of normal human phenotypes within the people of the British Isles - Meena, D (2018)
Genome-wide association studies have been of fundamental use in identifying common risk alleles with modest effects underlying multifactorial diseases such as diabetes, cancer, Crohn's disease as well as in polygenic traits, such as pigmentation, involving multiple genes. This thesis, using the GWAS approach, investigates the genetic basis of normal human traits such as human basal pigmentation, sensory perception and food preferences in a well-characterised population of the British Isles, with an emphasis on searching for variants with biologically, as well as statistically, significant effects. The data used in producing this text were collected as part of the "People of the British Isles" project. Out of 3702 samples, 2,912 were genotyped on the Illumina Human 1.2M-Duo genotyping chip (approximately 1,200,000 SNPs) as part of the Wellcome Trust Case Control Consortium 2 (WTCCC2) studies and the remaining samples were genotyped on Infinium OmniExpress-24 BeadChip array (approximately 750,000 SNPs) at the Wellcome Trust Centre for Human Genetics (WTCHG), Oxford. A total of 547,862 SNPs overlapped both genotyping chips. After genotype quality-control, there were 3,149 samples and 519,188 SNPs remaining for further analysis. Out of 3,149 samples, only 1,593 samples had phenotype and genotype data available. Fisher’s exact test was used to perform association analysis using PLINK (whole-genome data analysis toolset) and the statistical programming language R. In summary, 1,593 and 519,188 SNPs were used in the final genome- wide association analysis. Among the key features of this thesis are the population genetics data used in analysing different phenotypes. The sample collection criteria for recruiting participants genetically representative of geographic areas in rural Britain is of fundamental importance as it minimises the risk of spurious genotype-phenotype correlations that are due to population stratification. This research, in addition to confirming known genetic associations, presents a number of suggestive novel variants associated with hair and skin pigmentation which influence these complex phenotypes. For normal hair pigmentation, nearly all of the well documented pigmentation genes were replicated, including MC1R, SLC45A2, TYR, IRF4, HERC2, KITLG and SLC24A4 and results generally agreed with studies performed in the past. Replication of previous associations validates the PoBI dataset. Next, I demonstrate the genetic basis of bitter taste perception via identification of variants associated with the perception of phenylthiocarbamide (PTC), thiourea (PROP) and sodium benzoate tasting. Variants in the well-known taste receptor gene, TAS2R38 (rs1726866 and rs10246939), were successfully replicated in the PoBI data. I then focus on the genetic basis of preference for certain food items carefully selected to study the fondness for sweet, sour, bitter and salty tastes, and report novel genetic variants with strong biological evidence. Although none of the SNPs attained genome-wide significance for food preference data, some SNPs showed suggestive significance and were well-supported by available literature. The last part of this thesis provides new insights into the field of olfactory perception and argues for the potential link between neurological disorders and olfactory impairment. Most, if not all, novel variants (suggestive genome-wide significant) presented in this research have strong functional biological support behind the preliminary statistical observations and will be helpful in understanding the visible pigmentation differences among humans as well as the genetics underlying food preferences. In summary, I have taken advantage of a sampling criterion of having four grandparents from the same rural area, minimizing the risk of spurious genotype- phenotype correlations that are due to population stratification. Emphasis on careful collection and selection of the appropriate phenotypic categories has led to results that are both statistically and biologically persuasive, with large genetic effects.